Runtime monitoring of 5G network slicing using STAn - Panizo-Jaime, Laura; Gallardo-Melgarejo, María del Mar; Luque Schempp, Francisco; Merino-Gómez, Pedro (Elsevier, 2025)
"This work has been supported by the Spanish Ministry of Science and Innovation grant agreement PID2022-142181OB-I00 (LearnFDT) and the Spanish Ministry of Economic Affairs and Digital Transformation project TSI-063000-2021-11 (5G+TACTILE-1) and the European Union Horizon 2020 Smart Networks and Services Joint Undertaking (SNS JU) under grant agreement 101096328 (6G-SANDBOX)." The most recent technology in the evolution of mobile networks is 5G, which is aimed at offering differentiated quality of service (QoS) to specific groups of users or devices. Such groups could include public safety agencies, connected vehicles, citizens streaming video content, fixed Internet of Things devices, etc. Insofar as each group has different requirements in terms of bandwidth, latency, error rate, coverage or other relevant quality indicators, the network can be divided into multiple slices, with each slice supporting a group’s requirements. Such network slicing is becoming a key feature for telecom operators, who need to face the challenge of validating its correct behavior. In this paper, we propose a monitoring system to check that a 5G network is offering slicing in the proper way. To this end, we use the tool STAn, a general purpose runtime verification tool where the requirements to be monitored are expressed using temporal formulae. The paper identifies first a list of requirements that define the expected behavior of network slicing. Then, we describe how the initial logic eLTL supported by STAn is extended to the so-called eXtended Event-driven Temporal Logic (xeLTL) in order to represent the slicing requirements. Finally, we validate that the new version of STAn and the catalogue of xeLTL formulae are suitable to monitor and check if real 5G networks properly support slicing. This way, we provide a complete new system for runtime monitoring of 5G network slicing.
Keywords: Redes de ordenadores - Arquitecturas; Sistemas de comunicaciones inalámbricos; Sistemas expertos - Verificación; Network slicing; 5G network; Runtime verification; Runtime monitoring; Event-driven temporal logic